Considerations of sex in bioequivalence assessments: does sex affect pharmacokinetic variability between evaluation formulations? - Jang, Ji-Hun; Jeong, Seung-Hyun (European Journal of Clinical Pharmacology, 2025)
Background: Bioequivalence assessment determines the equivalence between drug formulations and is primarily used to demonstrate that a generic product is equivalent to its reference. The sex of the drug consumer is a major consideration in bioequivalence assessment, but specific ratios or absolute criteria for sex composition are usually not specified. Purpose: This study explored whether the sex of participants in a bioequivalence assessment could significantly affect the pharmacokinetic variability between formulations and decision outcomes. In bioequivalence studies, the sex composition should reflect the drug's target population, but it is often acceptable to limit it to healthy adult males. Therefore, it is essential to consider the variation in bioequivalence results according to sex. Methods: Levocetirizine and rabeprazole enteric-coated tablets were chosen as investigational agents, and clinical trial data for these were used in the bioequivalence analysis. This analysis was conducted both with and without considering sex, and the final determination of equivalence was based on whether the 90% confidence interval for the ratio of standard pharmacokinetic parameters between the reference and test formulations fell within the 80 to 125% range. Additionally, principal component analysis (PCA) was performed to determine whether there were significant differences in the targeted pharmacokinetic parameter values between drug formulations across each sex group. Results: Bioequivalence of levocetirizine's reference and test formulations was confirmed, independent of sex. For rabeprazole, bioequivalence was established in males—even without considering sex—but not in females, based on extended criteria for drugs with significant pharmacokinetic variability. The PCA results also showed that there were significant differences (P < 0.05) in the distribution of pharmacokinetic parameters of rabeprazole by gender and formulation. This indicates that equivalence assessments may vary based on pharmacokinetic differences related to sex among subjects in bioequivalence studies. Thus, it was shown that sex may influence pharmacokinetic variability between reference and test formulations of the same drug. Conclusion: This study provided valuable insights into the role of sex in bioequivalence studies. For drugs exhibiting significant pharmacokinetic differences between sexes, it is crucial to recognize that bioequivalence results may vary based on the sex ratio in the participant group. Therefore, further analysis and interpretation, taking sex-related factors into account, will be necessary during bioequivalence evaluations.